STUDI TENTANG PUSTAKAWAN PELAJAR AL-MURABBY - Siti Habibah, - (2019)
Keterlibatan pustakawan pelajar dalam penyelenggaraan perpustakaan sekolah dapat membantu tugas pustakawan sekolah dan membantu anggota pustakawan pelajar dalam memiliki rasa kepemilikan terhadap perpustakaan. Meski demikian, hasil studi pendahuluan menunjukkan keberadaan pustakawan pelajar di sekolah keagamaan tingkat Madrasah Aliyah (MA) hanya ada di MAN 1 Kota Bandung. Penelitian ini bertujuan untuk mengetahui model Pustakawan Pelajar Al-Murabby dengan mengkaji analisis kebutuhan pembentukannya, meliputi perekrutan dan penyeleksian, pembinaan, pengontrolan dan mengkaji gambaran kegiatannya meliputi tugas/ program kerja dan pemberian penghargaan. Pendekatan yang digunakan ialah kualitatif dengan metode studi kasus. Pengumpulan data dilakukan dengan menggunakan teknik wawancara, observasi dan studi dokumentasi. Informan penelitian ini terdiri dari key informan, pembina pustakawan pelajar, pustakawan, dan anggota pustakawan pelajar yang ditentukan melalui teknik purposive sampling.Teknik analisis data yang digunakan adalah reduksi data, display data dan penarikan simpulan. Hasil penelitian menunjukkan perekrutan Pustakawan Pelajar Al-Murabby dilakukan dengan memperkenalkan pustakawan pelajar, mengajak pelajar yang berminat menjadi pustakawan pelajar, dan pemberian formulir pendaftaran. Penyeleksinnya dengan melakukan wawancara terhadap pelajar yang mendaftar. Pembinaan dilakukan dengan pembinaan rutin dan pembinaan orientasi pustakawan pelajar. Pengontrolan dilakukan dengan melihat daftar hadir dan pengawasan program. Tugas/ program kerja Pustakawan Pelajar Al-Murabby yaitu pembaruan informasi mading, pegiat literasi, sharing, piket perpustakaan, dan terlibat dalam acara perpustakaan. Penghargaan yang diperoleh Pustakawan Pelajar Al-Murabby seperti memliki identitas pustakawan pelajar dan pemajangan foto pustakawan pelajar serta pemberian hak istimewa peminjaman buku perpustakaan. Diharapkan temuan penelitian ini dapat memberikan rujukan untuk pengembangan pustakawan pelajar di sekolah keagamaan Kota Bandung. Involvement of Student Librarians in organizing school libraries can help the task of library staff and help members of student librarians have a sense of ownership of the library. However, the results of the preliminary study show the existence of Student Librarians at the religious school level of Madrasah Aliyah (MA) only in MAN 1 Bandung City. This study aims to determine the model of the Al-Murabby Student Librarian by analyzing the analysis of its formation needs, including recruitment and selection, guidance, control and reviewing the description of its activities including work assignments / programs and awards. The approach used is qualitative with a case study method. Data collection is done using interview techniques, observation and documentation studies. The informants of this study consisted of key informants, student librarians, librarians, and student librarians who were determined through purposive sampling technique. Data analysis techniques used were data reduction, data display and conclusion drawing. The results showed that the recruitment of Al-Murabby Student Librarians was carried out by introducing student librarians, inviting students who were interested in becoming student librarians, and providing registration forms. Select it by interviewing students who register. Coaching is carried out with routine coaching and coaching the orientation of student librarians. Control is done by looking at the attendance list and monitoring the work program that is done. The assignments / work programs of the Al-Murabby Student Librarians are information updates, literacy activists, sharing, library pick-ups, and being involved in library events. Awards obtained by Al-Murabby Student Librarians such as possessing the identity of student librarians and displaying photos of student librarians and granting privileges for borrowing library books. It is hoped that the findings of this study can provide a reference for the development of student librarians in the Bandung religious school.